A hard carbon negative electrode material and its preparation method and application

By using starch -based hard carbon negative materials, the pore structure suitable for sodium ions is formed through cross -linking, aromatized and carbonization treatment, solving the sodium capacity and cycle stability of the existing sodium ion battery hard carbon negative materials. Insufficient problems realize high -efficiency sodium ion storage and stable cycle performance.

CN114497545BActive Publication Date: 2025-01-28GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111456775.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-01
Publication Date
2025-01-28
Estimated Expiration
2041-12-01

AI Technical Summary

Technical Problem

The hard carbon anode material of existing sodium ion batteries is difficult to achieve free embedding and detachment of sodium ions, resulting in insufficient sodium storage capacity and poor circulation stability.

Method used

The starch -based hard carbon negative material is used to form an internal pore structure through cross -linking and aromatization treatment to ensure that the laminar spacing is greater than 0.34nm, and a irregular pore structure is formed by carbonization treatment to adapt to the embedding and release of sodium ions.

Benefits of technology

The free embedding and departure of sodium ions is achieved, the sodium storage capacity and cycle stability are improved, and the excellent performance of the hard carbon negative electrode material is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003386879240000101
    Figure BDA0003386879240000101
  • Figure BDA0003386879240000111
    Figure BDA0003386879240000111
  • Figure HDA0003386879250000011
    Figure HDA0003386879250000011
Patent Text Reader

Abstract

The present invention discloses a hard carbon negative electrode material and a preparation method and application thereof. The base of the hard carbon negative electrode material is prepared with starch as raw material; the diameter of the internal pores of the hard carbon negative electrode material is larger than the diameter of the surface pores. The reasonable pore diameter and large interlayer spacing of the hard carbon negative electrode material are conducive to the insertion / extraction of sodium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery negative electrode materials, and in particular relates to a hard carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] With the decreasing supply of traditional fossil energy and the increasing environmental pollution, the development and utilization of energy is particularly important. Lithium-ion batteries have become the main energy storage devices in the field of consumer electronics due to their advantages such as high energy density, high voltage, low self-discharge and excellent cycle performance. However, there are few lithium resources on the earth, and the widespread use of lithium-ion batteries has made lithium resources more scarce and the price remains high, making them unsuitable for large-scale energy storage applications. Therefore, it is urgent to develop the next generation of energy storage battery systems with excellent comprehensive performance.

[0003] Sodium and lithium belong to the same group of elements, have similar physical and chemical properties, are abundant in reserves, and are cheap (natural alkali, the basic raw material of sodium, is about 30 to 40 times cheaper than lithium's raw material, lithium carbonate). + / Na) is higher than lithium ions (Li + / Li) is 0.3V higher, with more stable electrochemical performance and safety performance. However, the ionic radius of sodium ions (r = 0.113nm) is at least 35% larger than that of lithium ions (r = 0.076), making sodium ions relatively stable in the rigid lattice and difficult to reversibly deintercalate in the regular graphite structure, with almost no sodium storage capacity. Summary of the invention

[0004] The first technical problem to be solved by the present invention is:

[0005] Provided is a hard carbon negative electrode material having reasonable pore diameter and large interlayer distance that are conducive to the insertion / extraction of sodium ions.

[0006] The second technical problem to be solved by the present invention is:

[0007] Provided is a method for preparing the hard carbon negative electrode material.

[0008] The invention also provides a hard carbon negative electrode.

[0009] In order to solve the first technical problem, the technical solution adopted by the present invention is:

[0010] A hard carbon negative electrode material, wherein the base of the hard carbon negative electrode material is prepared using starch as a raw material;

[0011] The diameter of the internal pores of the hard carbon negative electrode material is greater than the diameter of the surface pores.

[0012] According to one embodiment of the present invention, the interlayer spacing of the hard carbon negative electrode material is greater than 0.34 nm.

[0013] The ion diameter of sodium ions is about R = 0.226nm, that is, the interlayer spacing of the negative electrode material must be at least greater than 0.226nm, so that theoretically sodium ions can be freely embedded and de-embedded in the negative electrode material layer, but in fact, the interlaced layered structure in the negative electrode material will affect the conduction of sodium ions to a certain extent. When the interlayer spacing of the negative electrode material reaches 0.34nm, it is still difficult for sodium ions to achieve free and reversible de-embedsion, so the interlayer spacing of the negative electrode material must be at least greater than 0.34nm.

[0014] According to one embodiment of the present invention, the interlayer distance of the hard carbon negative electrode material is about 3.828 nm.

[0015] According to one embodiment of the present invention, the diameter of the internal pores is X, 0<X≤5nm.

[0016] According to one embodiment of the present invention, the diameter of the internal pores of the hard carbon negative electrode material is between 0 and 5 nm. Within this range, it is conducive to the embedding and extraction of sodium ions, so that the hard carbon negative electrode material has both sodium storage capacity and cycle stability.

[0017] According to one embodiment of the present invention, the internal pores of the hard carbon negative electrode material are mainly 2 nm.

[0018] According to one embodiment of the present invention, the pore diameter of the surface of the hard carbon negative electrode material is smaller than the internal pores of the hard carbon negative electrode material, and the sodium ions can pass through the external pores of the hard carbon negative electrode material, but because the pore diameter of the surface is very small, substances larger than ions are difficult to pass through the external pores, thereby avoiding unnecessary impurities from being doped into the hard carbon negative electrode material, thereby ensuring a good sodium storage environment inside the hard carbon negative electrode material. In addition, there are a large number of irregular pores inside the spherical particles, which can further enhance the internal sodium storage capacity of the hard carbon negative electrode material.

[0019] According to one embodiment of the present invention, the hard carbon negative electrode material is subjected to a charge and discharge cycle test using a blue electric test cabinet, and the average sodium insertion capacity of the hard carbon negative electrode material is found to be 330 mAh / g.

[0020] According to one embodiment of the present invention, the starch is amylose and / or amylopectin; preferably at least one of potato starch, corn starch, wheat starch, sweet potato starch and cassava starch.

[0021] According to one embodiment of the present invention, the hard carbon negative electrode material is a spherical particle with a size of 15 to 20 μm. The spherical particle is of moderate size.

[0022] In order to solve the second technical problem, the technical solution adopted by the present invention is:

[0023] A method for preparing the hard carbon negative electrode material comprises the following steps:

[0024] The cross-linked starch is mixed with a thermally unstable polymer to obtain a precursor;

[0025] The precursor is subjected to aromatic ring treatment and carbonization treatment to obtain the hard carbon negative electrode material.

[0026] According to one embodiment of the present invention, the polymer includes at least one of polyethylene glycol, polyvinyl alcohol, sodium carboxymethyl cellulose, and nitrogen methyl pyrrolidone.

[0027] According to an embodiment of the present invention, the polymer may be a polymer powder or a polymer solution. When it is a polymer solution, its mass percent concentration is 0.5% to 20%.

[0028] The selected polymer will form a stable segment structure with starch and further promote starch cross-linking, and then, as the temperature of the reaction system rises, the segments of the polymer part in the system will decompose into volatile substances, so that an irregular pore structure is formed inside the hard carbon negative electrode material. As the temperature rises, the hard carbon negative electrode material will self-repair and repair the pores on the surface without affecting the formation of the internal pore structure.

[0029] Starch is composed of amylose and amylopectin. During the cross-linking process of starch, the hydrogen bond between amylopectin and amylose is broken due to the poor thermal stability of amylopectin, and amylopectin is decomposed. After the cross-linking process, the polymer is added, and the polymer and starch re-form a stable segment structure. As the temperature of the reaction system rises, the segments of starch and polymer move violently, the segments break, and then repolymerize to form an ether bond to connect the two segments. This process is equivalent to a process of further promoting starch cross-linking.

[0030] The volatile substances include water vapor, carbon monoxide, carbon dioxide, and alkane substances.

[0031] According to one embodiment of the present invention, the mass ratio of the polymer to the cross-linked starch is 0.05: 1 to 0.5: 1. Only under this mass ratio can the hard carbon negative electrode material be synthesized.

[0032] According to one embodiment of the present invention, when the polymer is a solution, the mass ratio of the polymer to the cross-linked starch is 0.5:1 to 2:1; when the polymer is a powder, the mass ratio of the polymer to the cross-linked starch is 0.05:1 to 0.5:1.

[0033] According to one embodiment of the present invention, the cross-linking treatment of the starch is carried out under the protection of an inert gas, wherein the inert gas is at least one of nitrogen, argon and helium, and the oxygen concentration during the cross-linking treatment of the starch is lower than 200 ppm.

[0034] According to one embodiment of the present invention, the starch is cross-linked at 200-235°C for 8-60h with a heating rate of 1-5°C / min. After the cross-linking, the starch is cooled to below 50°C.

[0035] The starch that has been cross-linked forms a spatial network structure. During the cross-linking process, a suitable cross-linking agent can be added to promote the hydroxyl reaction of starch molecules, thereby cross-linking multiple starch molecules.

[0036] Starch that has not been cross-linked will swell at medium temperatures and its structure will be destroyed, making it impossible to form pores.

[0037] According to one embodiment of the present invention, the temperature of the aromatic cyclization treatment is 300-500°C, the time is 2-6h, the heating rate is 3-5°C / min, and the aromatic cyclization treatment is under the protection of an inert gas, and the inert gas is at least one of nitrogen, argon and helium.

[0038] During the aromatic ring treatment, the chain segments of the polymer part in the precursor will decompose into volatile substances, so that an irregular pore structure is formed inside the hard carbon negative electrode material.

[0039] The method of using polymer to create pores can be applied not only to hard carbon material systems, but also to other carbonaceous systems, and has a wide range of applicability.

[0040] According to one embodiment of the present invention, the temperature of the carbonization treatment is 1000-1400°C, the time is 0.5-3h, and the heating rate is 3-5°C / min; the carbonization treatment is under the protection of an inert gas, and the inert gas is at least one of nitrogen, argon, and helium.

[0041] The purpose of the carbonization treatment is, on the one hand, to burn off excess organic matter and easily decomposable substances, and on the other hand, to make the hard carbon structure more stable; when the unstable medium in the material is decomposed, the material simultaneously performs self-repair, making the material structure more stable.

[0042] Starch biomass-based hard carbon materials were prepared by a three-step pyrolysis method and step-by-step sintering. Their disordered interlayer structure and large interlayer spacing are conducive to the insertion / extraction of sodium ions and exhibit excellent cycle stability.

[0043] In another aspect of the present invention, a hard carbon negative electrode is provided, comprising a copper foil and a slurry coated on the copper foil, wherein the slurry comprises a binder, a conductive agent and the hard carbon negative electrode material.

[0044] In another aspect of the present invention, a sodium ion battery is provided, comprising a sodium sheet positive electrode and a hard carbon negative electrode, wherein the hard carbon negative electrode comprises the hard carbon negative electrode material described above.

[0045] According to one embodiment of the present invention, after the hard carbon negative electrode is cycled 100 times at a rate of 0.1C, the average capacity is maintained at 83%.

[0046] One of the technical solutions described above has at least one of the following advantages or beneficial effects:

[0047] 1. The pore diameter of the surface of the hard carbon negative electrode material is smaller than the internal pores of the hard carbon negative electrode material. The sodium ions can pass through the external pores of the hard carbon negative electrode material, but since the pore diameter of the surface is very small, substances larger than ions are difficult to pass through the external pores, which avoids unnecessary impurities from being doped into the hard carbon negative electrode material, thereby ensuring a good sodium storage environment inside the hard carbon negative electrode material. In addition, there are a large number of irregular pores inside the spherical particles, which can further enhance the internal sodium storage capacity of the hard carbon negative electrode material;

[0048] 2. Starch biomass-based hard carbon materials were prepared by a three-step pyrolysis method and step-by-step sintering. Their disordered interlayer structure and large interlayer spacing are conducive to the insertion / extraction of sodium ions and exhibit excellent cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0050] Figure 1 Schematic diagram of the internal structure of the hard carbon negative electrode material in the embodiment.

[0051] Figure 2 This is the SEM image of the hard carbon negative electrode material in the embodiment. DETAILED DESCRIPTION

[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0053] The hard carbon negative electrode used in the test example includes a copper foil and a slurry coated on the copper foil, wherein the slurry includes a binder, a conductive agent and a hard carbon negative electrode material.

[0054] The battery used in the test example is a sodium ion button half-cell, the positive electrode is a sodium sheet, and the negative electrode is the above-mentioned hard carbon negative electrode.

[0055] Example 1

[0056] A method for preparing the hard carbon negative electrode material comprises the following steps:

[0057] (1) Dissolve 50 g of PEG-4000 (polyethylene glycol 4000) in 1000 ml of deionized water to prepare a 5% PEG-4000 polymer organic pore-forming solution;

[0058] (2) Under the protection of nitrogen, the corn starch is placed in a sintering furnace, the temperature is increased to 220° C. at a heating rate of 1° C. / min for 30 hours, and then cooled to 50° C. to obtain a sintered product;

[0059] (3) Take 100 ml of the 5% PEG-4000 polymer organic pore-forming solution of step (1) and 100 g of the calcined product of step (2), mix them evenly, and a precursor can be obtained;

[0060] (4) placing the precursor obtained in step (3) in a sintering furnace, heating the temperature to 400° C. at a heating rate of 3° C. / min under a nitrogen atmosphere, and performing an aromatic ring treatment for 3 hours;

[0061] (5) The sample after aromatic ring formation in step (4) is placed in a sintering furnace, and heated from 400°C to 1100°C at a heating rate of 5°C / min in a nitrogen atmosphere, and subjected to high-temperature carbonization treatment for 2 hours to obtain the above-mentioned hard carbon negative electrode material.

[0062] Example 2

[0063] A method for preparing the hard carbon negative electrode material comprises the following steps:

[0064] (1) Dissolve 50 g of PEG-4000 in 1000 ml of deionized water to prepare a 5% PEG-4000 polymer organic pore-forming solution;

[0065] (2) Under the protection of nitrogen, the corn starch is placed in a sintering furnace, the temperature is increased to 220° C. at a heating rate of 1° C. / min for 30 hours, and then cooled to 50° C. to obtain a sintered product;

[0066] (3) Take 100 ml of the 5% PEG-4000 polymer organic pore-forming solution of step (1) and 100 g of the calcined product of step (2), mix them evenly, and a precursor can be obtained;

[0067] (4) placing the precursor obtained in step (3) in a sintering furnace, heating the temperature to 300° C. at a heating rate of 3° C. / min under a nitrogen atmosphere, and performing an aromatic ring treatment for 3 hours;

[0068] (5) The sample after aromatic ring formation in step (4) is placed in a sintering furnace, and heated from 400°C to 1100°C at a heating rate of 5°C / min in a nitrogen atmosphere, and subjected to high-temperature carbonization treatment for 2 hours to obtain the above-mentioned hard carbon negative electrode material.

[0069] Example 3

[0070] A method for preparing the hard carbon negative electrode material comprises the following steps:

[0071] (1) Dissolve 50 g of PEG-4000 in 1000 ml of deionized water to prepare a 5% PEG-4000 polymer organic pore-forming solution;

[0072] (2) Under the protection of nitrogen, the corn starch is placed in a sintering furnace, the temperature is increased to 220° C. at a heating rate of 1° C. / min for 30 hours, and then cooled to 50° C. to obtain a sintered product;

[0073] (3) Take 100 ml of the 5% PEG-4000 polymer organic pore-forming solution of step (1) and 100 g of the calcined product of step (2), mix them evenly, and a precursor can be obtained;

[0074] (4) placing the precursor obtained in step (3) in a sintering furnace, heating it to 500° C. at a heating rate of 3° C. / min under a nitrogen atmosphere, and performing an aromatic ring treatment for 3 hours;

[0075] (5) The sample after aromatic ring formation in step (4) is placed in a sintering furnace, and heated from 400°C to 1100°C at a heating rate of 5°C / min in a nitrogen atmosphere, and subjected to high-temperature carbonization treatment for 2 hours to obtain the above-mentioned hard carbon negative electrode material.

[0076] Example 4

[0077] Compared with Example 1, step (2) of Example 4 is: under the protection of nitrogen, corn starch is placed in a sintering furnace, heated to 215° C. at a heating rate of 1° C. / min for 6 hours for cross-linking treatment, then heated to 225° C. at a heating rate of 1° C. / min for 12 hours, and cooled to 50° C. to obtain a sintered product. The remaining preparation steps are the same as those of Example 1.

[0078] Example 5

[0079] Compared with Example 1, step (2) of Example 5 is: under the protection of nitrogen, corn starch is placed in a sintering furnace, heated to 230° C. at a heating rate of 1° C. / min for 8 hours, and then cooled to 50° C. to obtain a sintered product. The remaining preparation steps are the same as those of Example 1.

[0080] Example 6

[0081] Compared with Example 1, the starch in Example 6 is potato starch. The preparation method is the same as that in Example 1.

[0082] Example 7

[0083] Compared with Example 1, the starch in Example 7 is wheat starch. The preparation method is the same as that in Example 1.

[0084] Example 8

[0085] Compared with Example 1, the polymer of Example 8 is polyvinyl alcohol. The preparation method is the same as that of Example 1.

[0086] Example 9

[0087] Compared with Example 1, the polymer of Example 9 is sodium carboxymethyl cellulose. The preparation method is the same as that of Example 1.

[0088] Example 10

[0089] Compared to Example 1, Example 10 has a different polymer concentration.

[0090] A method for preparing the hard carbon negative electrode material comprises the following steps:

[0091] (1) Dissolve 100 g of PEG-4000 (polyethylene glycol 4000) in 1000 ml of deionized water to prepare a 10% PEG-4000 polymer organic pore-forming solution;

[0092] (2) Under the protection of nitrogen, the corn starch is placed in a sintering furnace, the temperature is increased to 220° C. at a heating rate of 1° C. / min for 30 hours, and then cooled to 50° C. to obtain a sintered product;

[0093] (3) Take 100 ml of the 10% PEG-4000 polymer organic pore-forming solution of step (1) and 100 g of the calcined product of step (2), mix them evenly, and a precursor can be obtained;

[0094] (4) placing the precursor obtained in step (3) in a sintering furnace, heating the temperature to 400° C. at a heating rate of 3° C. / min under a nitrogen atmosphere, and performing an aromatic ring treatment for 3 hours;

[0095] (5) The sample after aromatic ring formation in step (4) is placed in a sintering furnace, and heated from 400°C to 1100°C at a heating rate of 5°C / min in a nitrogen atmosphere, and subjected to high-temperature carbonization treatment for 2 hours to obtain the above-mentioned hard carbon negative electrode material.

[0096] Embodiment 11

[0097] Compared to Example 1, Example 11 has a different polymer concentration.

[0098] A method for preparing the hard carbon negative electrode material comprises the following steps:

[0099] (1) Dissolve 150 g of PEG-4000 (polyethylene glycol 4000) in 1000 ml of deionized water to prepare a 15% PEG-4000 polymer organic pore-forming solution;

[0100] (2) Under the protection of nitrogen, the corn starch is placed in a sintering furnace, the temperature is increased to 220° C. at a heating rate of 1° C. / min for 30 hours, and then cooled to 50° C. to obtain a sintered product;

[0101] (3) Take 100 ml of the 15% PEG-4000 polymer organic pore-forming solution of step (1) and 100 g of the calcined product of step (2), mix them evenly, and a precursor can be obtained;

[0102] (4) placing the precursor obtained in step (3) in a sintering furnace, heating the temperature to 400° C. at a heating rate of 3° C. / min under a nitrogen atmosphere, and performing an aromatic ring treatment for 3 hours;

[0103] (5) The sample after aromatic ring formation in step (4) is placed in a sintering furnace, and heated from 400°C to 1100°C at a heating rate of 5°C / min in a nitrogen atmosphere, and subjected to high-temperature carbonization treatment for 2 hours to obtain the above-mentioned hard carbon negative electrode material.

[0104] Example 12

[0105] Compared to Example 1, Example 12 has a different polymer concentration.

[0106] A method for preparing the hard carbon negative electrode material comprises the following steps:

[0107] (1) Dissolve 200 g of PEG-4000 (polyethylene glycol 4000) in 1000 ml of deionized water to prepare a 20% PEG-4000 polymer organic pore-forming solution;

[0108] (2) Under the protection of nitrogen, the corn starch is placed in a sintering furnace, the temperature is increased to 220° C. at a heating rate of 1° C. / min for 30 hours, and then cooled to 50° C. to obtain a sintered product;

[0109] (3) Take 100 ml of the 20% PEG-4000 polymer organic pore-forming solution of step (1) and 100 g of the calcined product of step (2), mix them evenly, and a precursor can be obtained;

[0110] (4) placing the precursor obtained in step (3) in a sintering furnace, heating the temperature to 400° C. at a heating rate of 3° C. / min under a nitrogen atmosphere, and performing an aromatic ring treatment for 3 hours;

[0111] (5) The sample after aromatic ring formation in step (4) is placed in a sintering furnace, and heated from 400°C to 1100°C at a heating rate of 5°C / min in a nitrogen atmosphere, and subjected to high-temperature carbonization treatment for 2 hours to obtain the above-mentioned hard carbon negative electrode material.

[0112] Comparative Example 1

[0113] 100 g of corn starch was placed at 230°C for cross-linking treatment for 8 hours to obtain a starch precursor; the starch precursor was placed at 400°C for aromatization treatment for 2 hours and at 1100°C for high-temperature carbonization treatment for 3 hours, and then cooled to room temperature to obtain a hard carbon material.

[0114] In Comparative Example 1, since the raw materials used in the preparation do not contain polymers, there are almost no pores in the final hard carbon material.

[0115] Comparative Example 2

[0116] Compared with Example 1, the polymer of Comparative Example 2 is phenolic resin 2123. The preparation method is the same as that of Example 1.

[0117] In Comparative Example 2, since a polymer with good thermal stability is selected, there are almost no pores in the final product hard carbon material.

[0118] Performance Test:

[0119] The internal structure diagram of the hard carbon negative electrode material is as follows: Figure 1 As shown, its interior is a disordered interlayer structure and its exterior is distributed with microporous structures.

[0120] The SEM image (scanning electron microscope image) of the hard carbon negative electrode material prepared in Example 1 is as follows: Figure 2 As shown, the hard carbon negative electrode material is a spherical particle of 15 to 20 μm.

[0121] Table 1 shows the specific surface areas of the hard carbon products prepared in Examples 1, 2, 3 and Comparative Example 1. The specific data are obtained by testing with a Best Specific Surface Area Tester.

[0122] Table 1 Specific surface area of ​​hard carbon products

[0123]

[0124] As shown in Table 1, the specific surface area of ​​the hard carbon products prepared in Examples 1-3 is lower than that in Comparative Example 1, especially in Example 1, which is only 0.436 m 2 / g.

[0125] When starch is not pore-formed, there are some natural defects on the surface, resulting in a larger specific surface area. When polymers are added to the starch to form pores, the starch structure changes to a certain extent, voids appear inside, and the surface defects will repair themselves, thereby reducing the specific surface area.

[0126] During the preparation of Comparative Example 1, no corresponding polymer was added, so there was no combination of starch and polymer, and there was no step of decomposing the chain segments of the polymer part in the system during the heating process to form a pore structure.

[0127] Although Examples 1-3 all prepare starch biomass-based hard carbon materials through three-step pyrolysis and sintering, the different sintering temperatures result in different system reactions, which leads to differences in product structure and different sizes of pores inside and outside the hard carbon materials.

[0128] Table 2 shows the electrochemical properties of the hard carbon negative electrode for sodium ion batteries prepared in Examples 1, 2, 3 and Comparative Example 1. The specific data are obtained by testing in a blue electric test cabinet.

[0129] Table 2 Comparison of electrochemical performance of hard carbon negative electrode for sodium ion batteries

[0130]

[0131] As can be seen from Table 2, the electrochemical performance of the hard carbon products prepared in the examples is better than that of comparative example 1, especially example 1. The hard carbon product of comparative example 1 consumes part of the sodium ions to form a solid electrolyte film due to its large specific surface area, resulting in low initial charge and discharge efficiency and initial discharge specific capacity.

[0132] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A hard carbon negative electrode material, characterized in that: The base of the hard carbon negative electrode material is prepared using starch as raw material; The diameter of the internal pores of the hard carbon negative electrode material is greater than the diameter of the surface pores; The method for preparing the hard carbon negative electrode material comprises the following steps: The cross-linked starch is mixed with a thermally unstable polymer to obtain a precursor; The precursor is subjected to aromatic ring treatment and carbonization treatment to obtain the hard carbon negative electrode material; The starch cross-linking treatment is as follows: under the protection of inert gas, the starch is subjected to cross-linking treatment at 200-235° C. for 8-60 hours at a heating rate of 1-5° C. / min and maintained at an oxygen concentration below 200 ppm, and after the cross-linking treatment, the starch is cooled to below 50° C.; The aromatic ring treatment is as follows: under the protection of an inert gas, the precursor is placed at 300 to 500° C. for 2 to 6 hours at a heating rate of 3 to 5° C. / min; The carbonization treatment is carried out at a temperature of 1000-1400°C, for a time of 0.5-3h, at a heating rate of 3-5°C / min, and under the protection of an inert gas; The inert gas is at least one of nitrogen, argon and helium; The polymer includes at least one of polyethylene glycol, polyvinyl alcohol, sodium carboxymethyl cellulose and nitrogen methyl pyrrolidone.

2. A hard carbon negative electrode material according to claim 1, characterized in that: The starch is amylose and / or amylopectin.

3. A hard carbon negative electrode material according to claim 2, characterized in that: The starch is at least one of potato starch, corn starch, wheat starch, sweet potato starch and tapioca starch.

4. The hard carbon negative electrode material according to claim 1, characterized in that: The hard carbon negative electrode material is a spherical particle with a size of 15 to 20 μm.

5. The hard carbon negative electrode material according to claim 1, characterized in that: The diameter of the internal pores is X, 0<X≤5nm.

6. The hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the polymer to the cross-linked starch is 0.05:1 to 0.5:

1.

7. A sodium ion battery, characterized in that: It comprises a sodium sheet positive electrode and a hard carbon negative electrode, wherein the hard carbon negative electrode comprises a hard carbon negative electrode material as claimed in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Corn starch pyrolysis hard carbon electrode material preparation method

    CN110877908A